Algebra fuzzy norms generated by homomorphisms - Ali Reza Khoddami; Fatemeh Kouhsari (Journal of Mahani Mathematical Research)
‎‎‎As a new approach, for a nonzero normed algebra $A$, we will define some different classes of algebra fuzzy norms on $A$ generated by homomorphisms and continuous homomorphisms. Also as a source of examples and counterexamples in the field of fuzzy normed algebras, separate continuity of the elements within each class are investigated.